Molecular and cellular mechanisms in diabetic heart failure: Potential therapeutic targets - Mengstie, Misganaw Asmamaw; Abebe, Endeshaw Chekol; Teklemariam, Awgichew Behaile; Mulu, Anemut Tilahun; Teshome, Assefa Agegnehu; Zewde, Edgeit Abebe; Muche, Zelalem Tilahun; Azezew, Muluken Teshome (Frontiers in Endocrinology, 2022)
Diabetes Mellitus (DM) is a worldwide health issue that can lead to a variety of complications. DM is a serious metabolic disorder that causes long-term microvascular and macro-vascular complications, as well as the failure of various organ systems. Diabetes-related cardiovascular diseases (CVD) including heart failure cause significant morbidity and mortality worldwide. Concurrent hypertensive heart disease and/or coronary artery disease have been thought to be the causes of diabetic heart failure in DM patients. However, heart failure is extremely common in DM patients even in the absence of other risk factors such as coronary artery disease and hypertension. The occurrence of diabetes-induced heart failure has recently received a lot of attention. Understanding how diabetes increases the risk of heart failure and how it mediates major cellular and molecular alteration will aid in the development of therapeutics to prevent these changes. Hence, this review aimed to summarize the current knowledge and most recent findings in cellular and molecular mechanisms of diabetes-induced heart failure.